Assessing the Role of Market Share Development on Competitive Advantage in Dairy Companies - Taheri fard , Leila; Asayesh, Farzad; Rousta , Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aims to assess the role of market share development on competitive advantage in dairy companies. Method: The present research employs a mixed-methods approach (quantitative and qualitative). In the qualitative phase, purposeful sampling was conducted until theoretical saturation was achieved, and the statistical population, in accordance with the systematic pattern of Grounded Theory, included 12 experts in the fields of marketing and marketing managers in dairy companies. The Grounded Theory approach was utilized for qualitative data analysis and the presentation of a paradigm model using MAXQDA software, version 20. In the quantitative section, the population consisted of 730 employees of dairy companies, from which a sample size of 252 was selected using Cochran’s formula. Quantitative data were analyzed using descriptive statistics, inferential statistics, and structural equation modeling (with a Partial Least Squares approach) through Smart PLS 3.0 software. Findings: Based on the results of the qualitative analysis, 22 categories and 78 indicators were identified in six main groups: causal conditions (internal marketing, product life cycle management, market attractiveness, marketing mix, competitive strategy, planning and goal setting), contextual factors (customer characteristics, competitive environment, and market turbulence), core phenomenon (market share development strategy), strategies and actions (market share management, sales promotion, advertising, competition, brand equity, and market segmentation), intervening factors (risk management and sustainable competitive advantage), and outcomes (brand position consolidation, profitability, bargaining power, and market share increase). Conclusion: The results obtained in the quantitative section indicated that the proposed model of the research has adequate validity.